Foundations for a science of hypercomplexity I - Baraona Cockerell, Miguel (2023)
The indiscriminate use —and quite inconsistent— in the abusive repetition of words such as complexity, interdiscipline, and transdiscipline turns the intellectual terrain evoked by these vocables increasingly vacuous and useless. As so many other popular terms in the history of the Social Sciences during the XXth and XXIst centuries, whose conceptualization was weak buy attractive for its ubiquity which transformed them into intellectual they morphed into fashionable words with little or no usage or validity whatsoever for a rigorous analysis of social phenomena to which they were supposed to be applied. In this sketchy summary of ideas, we will propose a usage which we think will allow to establish and formulate in a more solid manner these notions (complexity, interdiscipline, transdiscipline), transforming them in conceptual instruments for analytic tasks in present day sociology, within the appropriate epistemological framework for the study of hypercomplex systems; which are, in fact, a superior and peculiar category of complex systems.